Improving access to emergency obstetric care in underserved rural Tanzania: a prospective cohort study - Angelo S. Nyamtema; Heather Scott; John C. LeBlanc; Elias Kweyamba; Janet Bulemela; Allan Shayo; Omary Kilume; Zabron Abel; Godfrey Mtey (BMC, 2022)
Abstract Background One of the key strategies to reducing maternal mortality is provision of emergency obstetric care services. This paper describes the results of improving availability of, and access to emergency obstetric care services in underserved rural Tanzania using associate clinicians. Methods A prospective cohort study of emergency obstetric care was implemented in seven health centres in Morogoro region, Tanzania from July 2016 to June 2019. In early 2016, forty-two associate clinicians from five health centres were trained in teams for three months in emergency obstetric care, newborn care and anaesthesia. Two health centres were unexposed to the intervention and served as controls. Following training, virtual teleconsultation, quarterly on-site supportive supervision and continuous mentorship were implemented to reinforce skills and knowledge. Results The met need for emergency obstetric care increased significantly from 45% (459/1025) at baseline (July 2014 - June 2016) to 119% (2010/1691) during the intervention period (Jul 2016 - June 2019). The met need for emergency obstetric care in the control group also increased from 53% (95% CI 49-58%) to 77% (95% CI 74-80%). Forty maternal deaths occurred during the baseline and intervention periods in the control and intervention health centres. The direct obstetric case fatality rate decreased slightly from 1.5% (95% CI 0.6-3.1%) to 1.1% (95% CI 0.7-1.6%) in the intervention group and from 3.3% (95% CI 1.2-7.0%) to 0.8% (95% CI 0.2-1.7%) in the control group. Conclusions When emergency obstetric care services are made available the proportion of obstetric complications treated in the facilities increases. However, the effort to scale up emergency obstetric care services in underserved rural areas should be accompanied by strategies to reinforce skills and the referral system.